A demodiversidade e as diferentes formas de democracia nos cursos de pedagogia e pedagogia do campo no Campus I da Universidade Federal da Paraíba - Lopes, Dougllas Pierre Justino da Silva (2022)
This research investigates the practice of Demodiversity in the Degree courses in Pedagogy and Pedagogy of Campo do Campus I of the Federal University of Paraíba. Its main objective is to identify the different contexts, spaces of conflict, continuities and discontinuities, which influence the production of knowledge for new democratic practices in Pedagogy and Education courses in Campo do Campus I of the Federal University of Paraíba. The research delimited as a space for research, the academic productions produced in the two undergraduate courses in the last two years, which addressed counter-hegemonic issues, such as gender, ethnic-racial, and people deprived of liberty and that evidence constructions of alternative democracies that make a counterpoint and act on abyssal lines, spaces in which the hegemonic power seeks to dominate at all times, for the maintenance of the power of Capital. The research makes a qualitative analysis, after screening several productions, of three course conclusion works, both in Pedagogy and in Rural Pedagogy and an experience report of my Teaching Internship I, carried out in the discipline Education, Solidarity Popular Economy and Associative Practices. The present investigation uses the author Boaventura de Souza Santos as theoretical and methodological foundations, approaches such as post-colonialism, dialoguing with several authors who work on the theme of Educational Policies and counter-hegemonic relations, preferably with authors from the UFPB itself and the Education Center and builds a translation, between absences and emergencies, for an ecology of the different knowledges that influence the analyzed experiences. The context of Influence of our work analyzes the current joint policy of Education and Educational Policies, with the historical context of the production of documents and regulations in Education, such as the National and State Plans for Education and Human Rights and the historical struggle for the protection of the rights of indigenous peoples, blacks and women, which have influenced various laws and policies such as Law No. . This analysis of data and documents, in dialogue with the various authors studied here, highlights the counter-hegemonic character of the Degree courses in Pedagogy and Rural Pedagogy, not seeking to transform it into utopia or romanticism, nor stating that the hegemonic power does not act in these spaces, through teaching and student practice, nor thinking that the path of imagining new democratic possibilities is easy, but that it is an obligation, based on internal pedagogical projects and national and international regulations, to always improve policies in education and of curricula for a University that is situated in the twelfth century, with its contradictions and specific and ever-changing demands.